2018
DOI: 10.1007/s41061-018-0187-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Simple Models for Molecular Simulation of Ethylene Carbonate and Propylene Carbonate as Solvents for Electrolyte Solutions

Abstract: Progress in understanding liquid ethylene carbonate (EC) and propylene carbonate (PC) on the basis of molecular simulation, emphasizing simple models of interatomic forces, is reviewed. Results on the bulk liquids are examined from the perspective of anticipated applications to materials for electrical energy storage devices. Preliminary results on electrochemical double-layer capacitors based on carbon nanotube forests and on model solid-electrolyte interphase (SEI) layers of lithium ion batteries are conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 119 publications
1
11
0
Order By: Relevance
“…Note however that, as in the case of mixed EC/PC clusters, Li + (PC)4 is more stable than the mixed structures. These findings are also in agreement with recent experimental studies by Seo et al31 .The structural properties of Li + (EC)n(PC)m and Li + (PC)n(DMC)m clusters (with m+n=4)…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Note however that, as in the case of mixed EC/PC clusters, Li + (PC)4 is more stable than the mixed structures. These findings are also in agreement with recent experimental studies by Seo et al31 .The structural properties of Li + (EC)n(PC)m and Li + (PC)n(DMC)m clusters (with m+n=4)…”
supporting
confidence: 93%
“…Although several experimental and theoretical works have focused on systems formed by pure EC, PC and DMC with the Li + ion [24][25][26][27][28][29][30][31] , solvation structure and dynamics of the cation in these solvents is still a subject of debate. More in details, Density Functional Theory (DFT) studies have shown that a (four-coordinated) tetrahedral geometry Li + (EC)4, is the dominant species [32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…Our simulation results of PS solutions reveal that structural and transport properties are subject to subtle interactions among ions and solvents molecules, which should be considered carefully when it comes to the design of electrolytes for Li/S batteries. 80 In the next step, studies on different types of anions in Li/PS solutions 81 as well as in confining electrode materials are envisioned.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of EC has been seldom reported in electrospinning process, probably due to its high boiling point of 248 °C . On the other hand, EC exhibits high dielectric constant (89.6 F/m) (see Supporting Information Table S1), which may play an important role in generating charges on the surface of the polymer solution during the electrospinning process . Several works have been focused on the use of high dielectric constant solvents as supplementary elements to produce finer fibers .…”
Section: Introductionmentioning
confidence: 99%